Strategi Keterampilan Penguatan Guru dalam Pembelajaran Pendidikan Agama Islam pada Anak Usia Dini - hestina wahyuni (Journal of Elementary School (JOES), 2023)
This research aims to see the results of implementing strengthening Islamic religious education learning with a strategy of strengthening teacher skills in learning Islamic religious education for early childhood at Pertiwi 1 Kindergarten, Bengkulu City. The method used is a qualitative descriptive research method, while the type of data used in this research is through observation, interviews and documentation. The results of the research show that the strategy for strengthening teacher skills in Islamic religious education learning uses Skinner's Operant Conditioning theory. Teachers provide verbal reinforcement in using words and sentences to praise, encourage, motivate, persuade, advise and reprimand children. Meanwhile, nonverbal reinforcement takes the form of gestures, touching, approaching, giving signs or symbols, and through Islamic religious education learning activities. This research proves that the implementation of teacher strengthening skills in learning Islamic religious education in early childhood is contained in the RPPH and teaching modules which are carried out by providing verbal reinforcement in using words and sentences, while non-verbal is in the form of gestures, touching, approaching, giving signs or symbols, and through activities for children so that children will be motivated in the good things they do. Keywords: Early Childhood, Reinforcement Skills, Islamic Education.